Perbedaan Makna Modalitas Kamoshirenai Dan Osore Ga Aru Pada Kalimat Berita - Fahma Amalia Hanifa; Guswara, Yahya Adhar; Malia Rahmatika; Al Ghazali, Ghaza Gibran (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
This research explores the diverse modalities within the structure of Japanese sentences, focusing on the modality of possibility known as "kanousei". Specifically, it delves into the distinctions between two forms of this modality: "kamoshirenai" and "osore ga aru," employing Iori's theory. Data collection involved the observational method, the basic technique used in this method is Simak Bebas Libat Cakap (SBLC), and taking notes as advanced techniques. 15 data points were gathered from news websites, comprising 8 sentences with the "kamoshirenai" modality and 7 with the "osore ga aru" modality. Subsequently, the data were analyzed using agih method. The analysis revealed that "kamoshirenai" expresses the possibility of an event, conveys the speaker's opinions or assumptions, and can indicate causal relationships. On the other hand, "osore ga aru" carries a similar meaning to "kamoshirenai," yet it nuances an undesirable outcome as perceived by the speaker.